Abnormal left ventricular systolic reserve function detected by treadmill exercise stress echocardiography in asymptomatic type 2 diabetes - Duan, Yuyou; Ye, Luwei; Shu, Qinglan; Huang, Yu; Zhang, Hongmei; Zhang, Qingfeng; Ding, Geqi; Deng, Yan; Li, Chunmei; Yin, Lixue; Wang, Yi (Frontiers in Cardiovascular Medicine, 2023)
Aims Subclinical left ventricular (LV) dysfunction may occur in T2DM patients at the early asymptomatic stage, and LV reserve function is a sensitive index to detect subtle LV dysfunction. The purpose of our study is (1) to assess the LV reserve function using treadmill exercise stress echocardiography (ESE) in asymptomatic type 2 diabetes mellitus (T2DM) patients; (2) to explore the link of serum biological parameters and LV reserve function. Methods This study included 84 patients with asymptomatic T2DM from September 2021 to July 2022 and 41 sex- and age-matched healthy controls during the corresponding period. All subjects completed treadmill ESE, LV systolic function-related parameters such as global longitudinal strain (GLS) and systolic strain rate (SRs), as well as diastolic function-related parameters such as E wave (E), early diastolic velocity (e′), E/e′ ratio, early diastolic SR (SRe), and late diastolic SR (SRa) were compared at rest and immediately after exercise. The difference between LV functional parameters after treadmill exercise and its corresponding resting value was used to compute LV reserve function. In addition, the associations of LV reserve function and serum biological parameters were analyzed. Results Patients with T2DM did not significantly vary from the controls in terms of alterations in LV diastolic reserve measures, the changes of LVGLS and SRs (ΔGLS: 2.19 ± 2.72% vs. 4.13 ± 2.79%, P < 0.001 and ΔSRs:0.78 ± 0.33 s−1 vs. 1.02 ± 0.28 s−1, P < 0.001) in the T2DM group were both lower than those in the control group. Glycated hemoglobin (HbA1c), N-terminal pro-brain natriuretic peptide (NTproBNP), waist circumference, and high-sensitive C-reactive protein (hsCRP) were identified as independent predictors of LV systolic reserve by stepwise multiple linear regression analysis. Conclusion LV systolic reserve function, as measured by pre- and post-exercise differences in GLS and SRs were significantly impaired in patients with asymptomatic T2DM, whereas diastolic reserve remained normal during exercise and was comparable to that of the control group. This was different from previous findings. High levels of HbA1c, NTproBNP, hsCRP, and increasing waist circumference were independent predictors of LV systolic reserve.